Volume 1: Turbomachinery 1988
DOI: 10.1115/88-gt-299
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Investigation of Fluid Flow for Disk Pumping Applications

Abstract: This paper describes numerically calculated results obtained for a viscous driven enclosed cavity flow and comparison with the experiments of Daly and Nece (Ref. 4). The sensitive prediction of moment coefficient is chosen for comparison purposes. Some discussion of the impact of k-ε turbulence modeling is also included. A second configuration demonstrating the degree of geometric complexity which can be handled is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Chew and Vaughn (1988) compared numerically predicted moment coefficients with the correlation of Daily and Nece and found good agreement over a wide range of Reynolds numbers. Roscoe, et al (1988) modelled the flow in a complex rotating cavity and found good agreement with Daily and Nece for the disk moment coefficient in both laminar and turbulent flow.…”
Section: Windage Modellingmentioning
confidence: 64%
“…Chew and Vaughn (1988) compared numerically predicted moment coefficients with the correlation of Daily and Nece and found good agreement over a wide range of Reynolds numbers. Roscoe, et al (1988) modelled the flow in a complex rotating cavity and found good agreement with Daily and Nece for the disk moment coefficient in both laminar and turbulent flow.…”
Section: Windage Modellingmentioning
confidence: 64%
“…Ke model has been used by many researchers in predicting the flow in various rotating cavities, e.g. Roscoe et al (1988) and Williams (1989), and it is extended to a multi-scale k-e model by Ko and Rhode (1991) in a rotating cavity flow and thermal calculation. In most of the above work, however, the cavity geometry is rather simple.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the above work, however, the cavity geometry is rather simple. Only Roscoe et al (1988) did a calculation on a cavity with complicated geometry as is in a turbomachine, but the reported results of this calculation were not extensive.…”
Section: Introductionmentioning
confidence: 99%
“…Examples for co-rotating disc systems are given by Chew (1985) and Morse (1988), and for rotor-stator disc systems by Chew and Vaughan (1988), Roscoe et al (1988) and Morse (1989).…”
Section: Introducfionmentioning
confidence: 99%